2017
DOI: 10.26603/ijspt20170921
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Segmental Rolling Ability and Lumbar Multifidus Activation Time

Abstract: Background:Segmental rolling has been utilized as an assessment and intervention tool to identify and affect dysfunction of the upper quarter, core, and lower quarter. One theory to explain dysfunctional segmental rolling is a lack of segmental spinal control / stabilization. Faulty muscle firing sequencing has been related to poor spinal stability, however to date, no assessment tool exists to evaluate a patient's motor coordination of local and global musculature. Purpose:The purpose of this study was to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…As a way of improving the integrated movements of the neck and shoulders, upper limb pattern rolling exercise can be performed in order to improve the neuromuscular control of the head, neck, and core muscles [21]. Previous studies have reported that there was a significant difference in the muscle activation time of the muscles around the hip according to the availability of upper limb pattern rolling exercise, and improvement of preliminary contraction of the stabilizing muscle through the performance of the upper limb pattern rolling exercise has been shown [22]. However, previous studies on the effect of neuromuscular control exercise (NMCE) of the upper limb pattern on the function of the neck are still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…As a way of improving the integrated movements of the neck and shoulders, upper limb pattern rolling exercise can be performed in order to improve the neuromuscular control of the head, neck, and core muscles [21]. Previous studies have reported that there was a significant difference in the muscle activation time of the muscles around the hip according to the availability of upper limb pattern rolling exercise, and improvement of preliminary contraction of the stabilizing muscle through the performance of the upper limb pattern rolling exercise has been shown [22]. However, previous studies on the effect of neuromuscular control exercise (NMCE) of the upper limb pattern on the function of the neck are still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…However, the multifidus plays a crucial role in spinal segmental stabilization among the back muscles. [33] Therefore, we believe that the analysis of the multifidus muscle holds significant clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…It directs to one of the points as stated by Clark, that the LM works eccentrically to allow lumbar flexion. 20 It suggests that increased or impaired activity of the lumbar multifidus can limit the flexion of the lumbar spine. A study found decreased activity in all extensor muscles of lumber including multifidus, in full flexion of lumbar among normal individuals.…”
Section: Discussionmentioning
confidence: 99%